Design of stearic acid/graphene oxide-attapulgite aerogel shape-stabilized phase change materials with excellent thermophysical properties. (March 2021) - Zhang, Ting; Zhang, Tuodi; Zhang, Jing; Zhang, Deyi; Guo, Pengran; Li, Hongxia; Li, Chunlei; Wang, Yi
Abstract: The large-scale commercial application of phase change materials (PCMs) was seriously limited by the leakage, poor heat storage capacity and slow thermal response behavior. To address these issues, stearic acid/graphene oxide-attapulgite aerogel (SA/HGA-ATP) shape-stabilized PCMs were fabricated via hydrothermal method. The morphology, structural characteristics, thermal properties were determined and the effects of ATP percentage on the thermal properties of confined SA were studied synchronously. The nanofibers of ATP intercalated among GO sheets via grafting modification and formed fiber-bridging 3D-network. Due to the enhanced loading interspaces and suppressed volumetric shrinkage of hybrid matrix, SA/HGA-ATP exhibited excellent thermal energy storage capacity (190.9 J g −1 ) and ultra-high SA contents (approx. 98 wt%) without leakage. The intercalated nanofibers sheltered the oxygen-containing groups of matrices, leading to the promotion of thermal energy storage performance with increase of ATP contents. Besides, the as-prepared PCMs displayed outstanding thermal response behavior because the interconnected and fiber-bridged matrices provided continuous thermal transfer pathway. Due to the protection of matrix, the composite PCMs also exhibited superior structure stability and incomparable thermal energy storage/release reliability. Considering the outstanding thermal-physical properties and low-cost of ATP, the SA/HGA-ATP has the potential to be applied in the fields of thermal energy storage, conversion and utilization. Highlights: Three-dimensional matrices with fiber-bridged porous structure were fabricated. Introduction of attapulgite nanofibers is benefit for serving more loading spaces. The constructed fiber-bridges provide continuous thermal-transfer pathway. The mass fraction of loaded stearic acid is as high as 98% without seepage.